ROLE OF BIOCHEMICAL MARKERS AMONG COVID-19 PATIENTS AND THEIR ASSOCIATION WITH SEVERITY OF DISEASE - RACHNA SABHARWAL; RAJESH MAHAJAN; PALLAVI MAHAJAN; FAYAZ AHMAD WANI; ANIMESH MAHAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The present study was aimed to evaluate the levels of biomarkers (D-dimer, Procalcitonin [PCT], lactate dehydrogenase [LDH], interleukin [IL]-6, and C-reactive protein [CRP]) among coronavirus disease 2019 (COVID-19) patients visiting/admitted in Government Medical College Jammu and analyze their association with the severity of disease. Methods: The study was conducted on 100 COVID-19-positive patients 18–75 years of age of either sex, visiting/admitted in Government Medical College Jammu, for a period of 6 months. The serum glucose levels, creatine phosphokinase, LDH, liver function tests, renal function tests, and various biochemical COVID-19 markers such as CRP, serum ferritin, IL-6, D-dimer, and PCT were analyzed. Results: In the present study, it was observed that when patients were divided according to the severity of disease, there was a significant difference in the mean levels of total bilirubin, serum sodium, serum potassium, D-dimer, SpO2, and duration of symptoms in a mild and severe group of patients, while there was no significant difference in the parameters such as IL-6, ferritin, CRP, PCT, LDH, and other routine biochemistry parameters. When a comparison was done between both the groups according to SpO2, only the mean levels of serum total bilirubin were significant. Conclusion: Thus, it is concluded that serum bilirubin was significantly elevated in mild, moderate, and severe groups of patients. Further research should be conducted to find some biomarkers which are specific to COVID-19 only.